Alam Bayu Travel & Tours / Muni Azuin Azmi ... [et al.] - Azmi, Muni Azuin; Hassan, Fizah; Mohd. Nor, Irna Watt; Azmi, Lilia Edlina; Abu Hassan, Norul Syuhada (Faculty of Accountancy, 2001)
Alam Bayu Travel & Tours is a progressive and innovative travel company, offering a made spectrum of services to the modern-day traveler, while providing personalized and professional services. We are travel agent specialized in various tour packages such as inbound, outbound, umrah and ziarah. Apart from those packages, we also provide the best in ticketing, visa application, hotel reservation, ready-made and tailor-made package .